Molecular& Antifungal Suceptibility Identification of Candida albicans Isolated from Samples of GIT Children with Diarrhea in Diyala Province Iraq (Indian Journal of Forensic Medicine & Toxicology, 2020)
Diarrheal diseases in children are a major public health concern in developing countries. especially speciesof Candida, responsible for causing candidiasis infection(diarrehea), require fast and accurate identification,The correct identification of Candida species is of great importance, as it presents prognostic and therapeuticalsignificance, allowing an early and appropriate antifungical therapy. This study was conducted to investigatethe incidence of Candida albicans associated with diarrhea in childrenThis study was included isolates of Candida spp. from stool of 100 patients samples with diarrhea and100 without diarrhea evaluated in AL-Batool Teaching Hospital by phenotypic methods , antifungalsusceptibility of C. albicans and determination of the C.albicans genotypes by Nested PCR, discriminatingC. albicans from the other Candida species. The tests used for phenotypic analysis were culture in SDA andCHROMAgar™ Candida, Phenotypic tests showed green colonies in chromogenic medium, The antifungalsusceptibility results of 43 C.albicans isolates present that all of Candida isolates tested were susceptibleto Amphotericin B and fluconazole (100%), while no resistance was observed in C.albicans toCaspofunginand Micafungin.Finally, only one isolate was resistant to flucytosine . Genomic DNAs of all C. albicans isolates wereamplified by PCR to detect their genotypes using. polymerase chian reaction amplification shows fourgenotypes(A,B,Cand D).A-genotype showed 4 subtypes and most common subgenotypes(1,3,4 and 5).